Poly(vinylidenefluoride)-hexafluoropropylene-methyl N-methylpyrrolidinium-N-acetate trifluoromethanesulfonylimide-lithium trifluoromethanesulfonylimide gel electrolytes - Kim, Ki-Sub; Lee, Seul Bee; Lee, Hyunjoo; Kim, Hoon Sik; Lee, Youngwoo; Kwack, Kwangsoo (ELSEVIER SCIENCE INC, 2009)
New polymer-ionic liquid-lithium salt gel electrolytes (PILGEs) were prepared using poly(vinylidenefluoride)-hexafluoropropylene copolymer (PVdF(HFP)), methyl N-methylpyrrolidinium-N-acetate trifluoromethanesulfonimide ([MMEPyr][TFSI]), and lithium trifluoromethanesulfonylimide (LiTFSI) in order to investigate the effects of ionic liquids containing an ester group on the electrochemical properties of polymer gel electrolytes. Free standing ionic gels consisting of PVdF(HFP), [MMEPyr][TFSI], and LiTFSI were prepared in a range of weight ratio of polymer/[MMEPyr][TFSI]/LiTFSI = 1/2/0.1 similar to 1. Ionic conductivities for the prepared PILGEs were measured with changing temperature and weight ratio of LiTFSI and the obtained values were found to be reasonable (10(-4) S cm(-1)) over the operating temperatures. (C) 2009 Published by Elsevier B.V. on behalf of The Korean Society of Industrial and Engineering Chemistry.
Keywords: IONIC LIQUIDS; MEMBRANES